1987
DOI: 10.1007/bf00148788
|View full text |Cite
|
Sign up to set email alerts
|

Energetic flare zones on the Sun

Abstract: In this investigation, we have studied the latitudinal, longitudinal (northern and southern hemispheric) distributions based on 1737 major flares observed during solar cycles 19 and 20 (see subsequent paragraphs) and have arrrived at some interesting results which go to show that as far major flares are concerned latitudewise 1'1-20 ~ belts, and longitudewise 5-8 places are most prolific in producing major flares in each hemisphere. During the above cycles at least 5 flare zones are present in each hemisphere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Years of marked activity on positive hemispheres (northern, eastern) are followed by others of greater activity on negative hemispheres (southern, western). This confirms previous results found by Bell (1962), Waldmeier (1971), Roy (1977), Verma et al (1987), Heras et al (1990) and Joshi (1995). The solar surface has been divided in several ways and the efficiency in sfe production has been checked for each region.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Years of marked activity on positive hemispheres (northern, eastern) are followed by others of greater activity on negative hemispheres (southern, western). This confirms previous results found by Bell (1962), Waldmeier (1971), Roy (1977), Verma et al (1987), Heras et al (1990) and Joshi (1995). The solar surface has been divided in several ways and the efficiency in sfe production has been checked for each region.…”
Section: Discussionsupporting
confidence: 88%
“…An extra emission of particles and radiation then takes place (although not always both phenomena are coincident). Particles spend about one or more days travelling from Sun to Earth, producing magnetic storms and aurora at their encounter with the Earth's magnetosphere; but radiations have a prompt effect on Earth by ionizing the upper layers of the atmosphere (Švestka, 1976;Verma et al, 1987). Solar flare effects (sfe, also called magnetic crochets) are events directly related to an enhancement in the solar radiation that produces an increase in the electric conductivity and currents in the ionosphere, and finally a magnetic signature at ground level (Curto et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…The flares mostly occurred within ±30 ∘ latitudes. Verma et al (1987) found that during solar cycles 19 and 20, the 11 to 20 degree latitudes are most prolific in northern and southern hemispheres for occurrence of major flares. Garcia (1990) found that during cycles 20 and 21 majorities of the flare events (M≥ 1) occurred within ±30 ∘ latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Solar activity indications do not occur evenly on the solar disk. It is well known that many types of solar phenomena exhibit some N−S asymmetry distributions (Reid 1968;Hansen & Hansen 1975;Roy 1977;Swinson et al 1986;Verma 1987;Verma et al 1987;Garcia 1990;Oliver & Ballester 1994;Atac & Ozguc 1996;Joshi 1995;Heras et al 1996). One of the first studies concerning the N−S asymmetry was made by Newton & Milson (1955), who studied the distribution of the yearly values of sunspot areas from 1874 to 1955.…”
Section: Introductionmentioning
confidence: 99%